Peran Kedalaman Keuangan Islam dalam Menghubungkan Tata Kelola dan Ketahanan Ekonomi: Bukti dari 26 Anggota IFSB - Novianti, Catur; Elina, Riskiana; Zain, Nurafifah; Suhendi, Suhendi; Yulianti, Yulianti (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2025)
This study aims to analyze the effect of Institutional Quality, Economic Freedom, and Technology on Economic Resilience with Islamic Financial Depth (IFD) as a mediating variable in 26 member countries of the Islamic Financial Services Board (IFSB) during the period 2014-2023. This study uses a quantitative approach with panel data regression method and Sobel Test mediation test. The analysis shows that Institutional Quality has a significant direct effect on Economic Resilience, but has no significant effect on IFD. Meanwhile, Economic Freedom shows a significant indirect effect on Economic Resilience through the mediation of IFD. In contrast, Technology does not show a significant effect either directly or indirectly on Economic Resilience. These results confirm that the depth of the Islamic financial sector plays an important role as an intermediary mechanism in strengthening the influence of economic policy on national economic resilience.